1992
DOI: 10.1007/bf02245166
|View full text |Cite
|
Sign up to set email alerts
|

Genetic differences in the rewarding and activating effects of morphine and ethanol

Abstract: The influence of genotype on the rewarding and locomotor activating effects of morphine and ethanol was examined in the place conditioning paradigm. Two inbred mouse strains (C57BL/6J and DBA/2J) were exposed to a differential conditioning procedure in which each mouse received four pairings of a distinctive floor stimulus with IP injection of morphine (0, 2.5, 5 or 10 mg/kg) or ethanol (0, 1, 2, 3 or 4 g/kg). A different floor stimulus was paired with saline. Conditioning trials lasted 30 min and each experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

41
184
7

Year Published

1995
1995
2011
2011

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 252 publications
(232 citation statements)
references
References 41 publications
41
184
7
Order By: Relevance
“…The mice of C57BL/6J (B6) strain were initially described to display low or complete lack of alcohol-induced CPP (Cunningham et al, 1992). However, later studies have shown that the place preference can be induced to B6 mice by increasing the number of conditioning sessions with alcohol (Risinger et al, 2001;Boyce-Rustay and Risinger, 2003).…”
Section: Discussionsupporting
confidence: 42%
“…The mice of C57BL/6J (B6) strain were initially described to display low or complete lack of alcohol-induced CPP (Cunningham et al, 1992). However, later studies have shown that the place preference can be induced to B6 mice by increasing the number of conditioning sessions with alcohol (Risinger et al, 2001;Boyce-Rustay and Risinger, 2003).…”
Section: Discussionsupporting
confidence: 42%
“…This dose is somewhat lower than those previously reported to induce CPP in mice. Cunningham et al (1992a) reported a maximal conditioning effect with doses of 3 and 4 g/kg using DBA/2J mice, whereas demonstrated significant CPP in Swiss-Webster mice with ethanol doses of 1 and 2 g/kg. The higher potency of ethanol in our study compared with the previous reports might be explained by the shorter conditioning trials used in the present study (20 min) compared with 30 and 60 min in the cited study .…”
Section: Discussionmentioning
confidence: 44%
“…The floor of the open field consisted of two interchangeable halves made of one of two textures: either a 'grid' made from stainless-steel rods (2.3 mm stainless-steel rods mounted 6.4 mm apart) or 'hole' floor (16-gauge stainless steel perforated with 6.4-mm diameter holes). This combination of floor textures was selected on the basis of unpublished pilot studies using commercially acquired C57BL/6 mice and studies by others (Cunningham et al, 1992;Cunningham, 1995) showing that mice spend an average of about 50% time on each floor type during (preconditioning) bias/preference tests. Thus, the apparatus allowed for an 'unbiased' place preference procedure to be used (see 'Results').…”
Section: Apparatusmentioning
confidence: 44%